Pengaruh Role Conflict dan Role Ambiguity terhadap Kinerja Auditor dengan Kecerdasan Intelektual sebagai Variabel Moderasi - Alma Pratiwi; Kartini Kartini; Aini Inrijawati (Politeknik Ganesha Medan, 2023)
This study aims to examine the effect of role conflict and role ambiguity on auditor performance with intellectual intelligence as a moderating variable. The population in this study are all auditors who work in the office of the Inspectorate of South Sulawesi Province. The total population in this study is 45 people. Because the population in this study is less than 100, the sample selection method to be used is the saturated or census sampling method where all members of the population are sampled. This study used primary data by conducting direct research in the field by giving questionnaires or question sheets to 45 respondents. The data analysis method uses the partial least squares method with a structural equation model approach to examine the effect of role conflict and role ambiguity on auditor performance with intellectual intelligence as a moderating variable. The results of the study show that the role conflict variable has a negative and significant effect on auditor performance; the variable role ambiguity has a negative and significant effect on auditor performance; intellectual intelligence can moderate the effect of role conflict on audit performance; and intellectual intelligence cannot moderate the effect of role ambiguity on audit performance.